PENINGKATAN KUALITAS KAYU SAWIT DENGAN PERLAKUAN KOMPREGNASI MENGGUNAKAN TANIN RESORSINOL FORMALDEHIDA - Okti Rachmawati; Purwantiningsih Sugita; Adi Santoso (Jurnal Penelitian Hasil Hutan, 2018)
Indonesia is one of the largest palm oil producers in the world. The availability of oil palm trunk as a waste of the final crop-harvesting is enormous, inexpensive, and can be a source of sustainable alternative wood for various applications if it can be utilized properly. The weaknesses of oil palm wood characteristics are low in specific gravity, as well as physical and mechanical properties compared to other biomaterial especially wood. This paper studies the oil palm wood quality improvement through compregnation technique using tannin recorcinol formaldehyde (TRF). The study was carried out by coating sample surface of oil palm wood (5 cm × 5 cm × 2 cm) with TRF adhesive composition 1:0.05:0.05 (v/v/v) and followed by cold pressing for 10 mins at 10 kg/cm2 pressure and then followed by hot pressing at 120oC and pressure of 12 kg/cm2 for 10 minutes. Density, hardness, thickness swelling as well as formaldehyde emission, were measured and compared to controls. Results showed that the compregnated wood significantly increased its density by 104.61%, and its hardness by six folds, and the thickness swelling decreased by 85.98%. The compregnated oil palm wood has also increased in strength quality, i.e from strength class V to III.